Rap it up, share it up: Identity politics of youth "social" movement in Moroccan online rap music. (May 2019) - Ben Moussa, Mohamed
This study examines the discursive and artistic expression of Moroccan youth identity politics through the production and consumption of rap music online, particularly on YouTube. Drawing on multimodal discourse analysis (MDA), the study explores textual, visual, and reception modes and discourses of Moroccan rap songs mediated through songs' lyrics, video clips, and user comments on the video sharing platform. Focusing on four levels of discourse, namely, narrative and interpersonal representation, genre, modality, and style, the study examines the following key questions: What are the discourses that emerge from the production, circulation, and consumption of online rap music by Moroccan youth? How do online rap production and reception contribute to identity formation among Moroccan youth? To what extent does online rap music contribute to the development of a progressive and alternative social youth movement that challenges dominant cultural and political power relations?